Upaya Guru dalam Mengembangkan Karakter Peduli Sosial Peserta Didik SD Pada Mata Pelajaran IPS di Masa Pandemi COVID-19 - Muharani, Ruly Watipah; Saputra, Yudha Munajat; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
The study was based on concerns about the loss of social character in learners during the Covid-19 pandemic conditions. The character of social care is a character attitude that must be implemented by the teacher to the learners. The purpose of the study was to know the teacher's efforts, obstacles and solutions, as well as to know the results of the efforts made by teachers in developing the social caring character of primary school learners in IPS subjects during pandemics. The use of this method in this study is a survey method with a sample of teachers from 5 elementary school in Cisarua Subdistrict, Sumedang. The Study found that teachers always strive to develop the character of students' social care by starting from learning planning to getting results that are in accordance with the expected. As for the obstacles faced but can be solved with the solutions offered.